PENGARUH PELATIHAN DAN PENGEMBANGAN KARIER TERHADAP KINERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA TANGERANG SELATAN - Lestari, Suci; Paeno (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of training and career development on employee performance at the South Tangerang City Population and Civil Registration Service, both partially and simultaneously. The method used in this method is quantitative, the population used was 122 people with a sample of 93 respondents. This research instrument has 30 statement items from the variables of training, career development and employee performance. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, determination analysis and hypothesis testing. Based on the analysis results, the multiple regression value was obtained, namely: Y = 9.037 + 0.333 X1+ 0.477 X2 with an R value (correlation coefficient) of 0.882. This means that the training variables (X1) and career development (X2) simultaneously have a strong relationship with the employee performance variable (Y). The R value (coefficient of determination) is 0.744 or 74.4% while the remaining 25.6% is influenced by other factors. Hypothesis testing obtained a value of Fcount > Ftable (130.509 > 3.10). This was also confirmed by a significance value of 0.000 < 0.05 so it was concluded that H0 was rejected and H3 was accepted. It can be concluded that training (X1) and career development (X2) simultaneously have an acceptable effect on employee performance (Y).